(Non) è stata la mano di Dio. Il film “La Scuola Cattolica” vietato ai minorenni dalla Commissione di revisione cinematografica (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Titoli di testa: introduzione e una premessa di metodo - 2. La vicenda: il caso de “La Scuola Cattolica” - 3. La questione aperta: un divieto amministrativo a tutela del sentimento religioso cattolico? - 4. La decisione: la sentenza del TAR Lazio n. 12795 del 2021 - 5. Titoli di coda: considerazioni conclusive.It was (not) the hand of God. The movie “La Scuola Cattolica” prohibited to minors by the Film Review CommissionABSTRACT: On 4 October 2021, the Italian movie "La Scuola Cattolica” (The Catholic School) got a ban on minors under 18 years of age. In this connection, the Italian Film Review Commission argued that the ban was necessary to prevent youth from consuming material deemed to be ‘harmful’ to their emotional and psychological sensibilities. This paper rejects the commissioners’ reasoning, to then introduce and defend the claim that the case of “La Scuola Cattolica” is instead about religiously-motivated movie censorship. Crossing borders between law and anthropology, here the goal is to demonstrate how the grievances behind the screening of “La Scuola Cattolica” concern ‘religious insult’ rather than advocacy of child protection.